Evaluation of some integrated management approaches against flower thrips and pod borers of mungbean (Vigna radiata L.) - Hossain, Md Altaf; Sarker, MA; Azam, MG (Jahangirnagar University Journal of Biological Sciences, 2018)
Efficacy and profitability of different management packages comprising white sticky trap, biopesticide and synthetic insecticides were evaluated against flower thrips and pod borers of mungbean at Pulses Research Center, Ishurdi, Pabna, Bangladesh during two consecutive seasons of kharif-1, 2015 & 2016. All the treatments significantly reduced flower infestation by thrips and pod borer infestation. The highest percentage of flower infestation and thrips population reduction was observed in installing white sticky trap + spraying of chlorfenapyr (Intrepid 10 SC) + spraying with emamectin benzoate (Proclaim 5 SG) followed by farmers practice, i.e. spraying imidacloprid (Imitaf 20 SL). Again, the highest pod borer infestation reduction was found in installing white sticky trap + spraying azadirachtin (Bio-neem plus 1EC) + spraying with spinosad (Success 2.5 SC) treated plots followed by installing white sticky trap + spraying chlorfenapyr (Intrepid 10 SC) + spraying with emamectin benzoate (Proclaim 5 SG). The highest grain yield was obtained from installing white sticky trap + spraying chlorfenapyr (Intrepid 10 SC) + spraying with emamectin benzoate (Proclaim 5 SG), but the highest return came from farmers practice (spraying Imidacloprid). This might be due to the higher cost of Intrepid 10 SC and Proclaim 5 SG reduced the return as well as benefit. Therefore, considering the efficacy and benefit, it is seen that the evaluated IPM package could not be profitable against low level infestation of flower thrips and pod borer infestation. It could be profitable that areas where serious out break of flower thrips and pod borer occurs. Jahangirnagar University J. Biol. Sci. 7(1): 55-64, 2018 (June)